Pulmonary vasodilator strategies in neonates with acute hypoxemic respiratory failure and pulmonary hypertension. Issue 4 (August 2022) - Cookson, Michael W.; Abman, Steven H.; Kinsella, John P.; Mandell, Erica W.
Abstract: The management of acute hypoxemic respiratory failure (AHRF) in newborns continues to be a clinical challenge with elevated risk for significant morbidities and mortality, especially when accompanied with persistent pulmonary hypertension of the newborn (PPHN). PPHN is a syndrome characterized by marked hypoxemia secondary to extrapulmonary right-to-left shunting across the ductus arteriosus and/or foramen ovale with high pulmonary artery pressure and increased pulmonary vascular resistance (PVR). After optimizing respiratory support, cardiac performance and systemic hemodynamics, targeting persistent elevations in PVR with inhaled nitric oxide (iNO) therapy has improved outcomes of neonates with PPHN physiology. Despite aggressive cardiopulmonary management, a significant proportion of patients have an inadequate response to iNO therapy, prompting consideration for additional pulmonary vasodilator therapy. This article reviews the pathophysiology and management of PPHN in term newborns with AHRF while highlighting both animal and human data to inform a physiologic approach to the use of PH-targeted therapies.